Control of hydrogen content and fuel recycling for long pulse high performance plasma operation in EAST. (16th October 2019) - Yu, Y.W.; Hu, J.S.; Zuo, G.Z.; Sun, Z.; Wang, L.; Xu, W.; Wang, J.R.; Cao, B.; Gao, W.; Xu, J.C.; Li, J.G.
Abstract: Control of fuel recycling and hydrogen content in the Experimental Advanced Superconducting Tokamak (EAST) using various methods is studied for high-power long pulse high confinement mode (H-mode) plasma operation. The results show that long duration first wall baking and discharge cleaning in EAST provides the necessary clean vacuum environment with a high ultimate vacuum of 3.6 × 10 −6 Pa and low outgassing rate of 1.5 × 10 −4 Pa m 3 s −1 for plasma operation. In-vessel cryopumps are found to provide an efficient method for particle recycling control in the divertor region to decrease global recycling coefficient ( R global ) from 1.0 to 0.8 during ohmic heating plasmas, and it provides a high particle exhausting rate of 10 20 –10 21 D-atoms s −1 in high-power plasma operations. Long duration silicon coating is found to be more powerful than baking and discharge cleaning, which reduces the H/(H + D) ratio gradually to a value as low as 8%, and lithium coating is more effective and more efficient than silicon coating, to further reduce the H/(H + D) ratio to 3%. Real-time lithium powder injection is a novel method for recycling control, which reduces R global from 0.94 to 0.82 under lithium coating wall conditioning. By the combination and optimization of the above methods, H-mode plasmas with low hydrogen content and low fuel recycling have been achieved in EAST and have been extended gradually to 101 s in 2017. Recycling flux has even decreased gradually during 101 s H-mode plasmas due to increased first wall temperature and the resulting increased Li-II emission. These results provide valuable references on hydrogen content and fuel recycling control for long pulse H-mode plasmas of up to 400–1000 s with high-power heating in EAST and future fusion devices.